Healthy living environment in Kuala Lumpur public parks - Hj. Baharuddin, Zainul Mukrim (ulliyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Providing a healthy living environment is one of the key issues for planners and designers. Various urban design and planning approaches have been debated worldwide to provide healthy living. Rapid urbanization and its impact on social, environmental and health quality. These issues are more acute in developing countries than in developed countries. Urban public parks offer many opportunities for urban dwellers to achieve a healthy living environment. Thus, this paper investigates people’s interaction with open space and the benefits of urban parks in Kuala Lumpur. Opinions of visitors from the nine urban parks in Kuala Lumpur were collected to address the aim of the research. Various levels of urban park such as the city parks, district and neighborhood parks were investigated. The parks represent all five districts in Kuala Lumpur. Altogether, 47 respondents were interviewed at seven parks. Information collected through the interview survey was analyzed using qualitative analysis techniques.